Book Review: “Society and Sociology in Bangladesh: A South Asian Perspective” by Sadeka Halim, ASM Amanullah, and Rasheda Irshad Nasir (Editor) - Rahman, Md. Masudur; Khatun, Khadiza (Global South Review, 2025)
The book review has no abstract